Severe ASIA syndrome associated with lymph node, thoracic, and pulmonary silicone infiltration following breast implant rupture: experience with four cases. (April 2015) - Nesher, G; Soriano, A; Shlomai, G; Iadgarov, Y; Shulimzon, T R; Borella, E; Dicker, D; Shoenfeld, Y
Silicone has been considered biologically inert; thus it has been employed in many medical devices and nowadays is commonly used in plastic surgery for mammary prosthesis. It is well tolerated in most cases. However, autoimmune disorders and siliconomas with granulomatous reactions after silicone implant rupture have been described. We report cases of four women who developed systemic disorders following rupture of silicone breast implants resulting in lymph node and thoracic silicone infiltration. The symptoms in these cases, including arthralgia, myalgia, generalized weakness, severe fatigue, sleeping disturbances, cognitive impairment, memory loss, irritable bowel syndrome, and weight loss, clearly match the criteria of the recently defined autoimmune/inflammatory syndrome induced by adjuvants (ASIA).